2020
DOI: 10.1039/d0ee00047g
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the carbon balance for CO2 electroreduction on Cu using gas diffusion electrode reactor designs

Abstract: The carbon balance during high-rate CO2 reduction in flow electrolyzers was rigorously analyzed, showing that CO2 consumption should be taken into account for evaluating catalytic selectivity of gas products.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
436
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 385 publications
(455 citation statements)
references
References 53 publications
14
436
3
2
Order By: Relevance
“…4C, this result was also validated by GC-BID measurements). This is very similar to what was observed in a similar cell with Sustainion s membrane, 28,29 confirming that the negative charges are exclusively transported through the PiperION membrane by CO 3 2À ions. The overall mass balance is depicted in Fig.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…4C, this result was also validated by GC-BID measurements). This is very similar to what was observed in a similar cell with Sustainion s membrane, 28,29 confirming that the negative charges are exclusively transported through the PiperION membrane by CO 3 2À ions. The overall mass balance is depicted in Fig.…”
supporting
confidence: 85%
“…from OH À in a CO 2 rich environment. 28,29 This observation suggests that a membrane with high carbonate/bicarbonate conductivity is a prerequisite for high current density AEM CO 2 electrolysis. This might seem counter-intuitive, as carbonate conduction leads to reactant loss to the anode, which on the system level invokes extra costs associated with the regeneration of the anolyte, and/or CO 2 separation/loss from the anode gas.…”
Section: àmentioning
confidence: 93%
“…18,19 By using GDE-type ow electrolyzers, the mass-transport of CO 2 and gaseous products on the surface of the catalysts can be accelerated, achieving commercially relevant current densities (>100 mA cm À2 ) along with high selectivity toward a desired product. [20][21][22][23][24][25][26][27][28][29] To date, most of the high-rate CO 2 reduction studies based on GDE-type ow electrolyzers have been performed using anion exchange membranes (AEMs). [20][21][22][23][24][25][26][27][28][29] However, our recent work demonstrated a substantial crossover of anionic CO 2 reduction products such as acetate and formate through AEMs in GDE-type ow electrolyzers.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29] To date, most of the high-rate CO 2 reduction studies based on GDE-type ow electrolyzers have been performed using anion exchange membranes (AEMs). [20][21][22][23][24][25][26][27][28][29] However, our recent work demonstrated a substantial crossover of anionic CO 2 reduction products such as acetate and formate through AEMs in GDE-type ow electrolyzers. 29 More importantly, aer the electrolytes reach a steady state, it was found that about 70% of the consumed CO 2 is captured at the cathode/electrolyte interface via reaction with OH À , forming CO 3 2À , which is transported to the anolyte via an AEM as a charge-carrier.…”
Section: Introductionmentioning
confidence: 99%
“…52,53 For an optimum 90% CO2 capture efficiency, 0.354 kWh/kg CO2 captured was considered. 54 We note that this value is approximately one quarter of the energy required for a standalone (without heat integration) monoethanolamine based CO2 capture process (~1.2 kWh/kg CO2 captured), 52,61 due to efficient heat integration with steam cycle to regenerate the solvent. 55 Based on electrochemical CO2 reduction reaction stoichiometry (Table 1), we calculated the required capture energy per mass (kWh/kg product) for each product.…”
Section: Post Combustion Co2 Capturementioning
confidence: 99%